2019
DOI: 10.1021/acschemneuro.9b00341
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Decrease of the Endogenous SIRT3 and Increases of Acetylated Proteins in Scrapie-Infected Cell Line SMB-S15 and in the Brains of Experimental Mice

Abstract: The linkage between mitochondrial dysfunction and neurodegenerative diseases including prion diseases has been frequently reported. As the major deacetylase in mitochondria, SIRT3 plays a crucial part in regulating the function of many mitochondrial proteins. Although SIRT3 was reported to be linked to several neurodegenerative diseases, it is still unknown if SIRT3 is involved in prion diseases. In this study, we have presented a substantially declined status of mitochondrial SIRT3 in both the levels of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Previously, we have described that the levels and activities of Sirt1, a class III histone deacetylase, were remarkably decreased in the brains of different scrapie infected rodent models and in a prion infected cell line SMB-S15, resulting in increases of the acetylating forms of some Sirt1 target proteins, such as P53, PGC-1, and STAT3 [19]. Recently, we have also con rmed the declined levels of Sirt3 in the brain tissues of several scrapie infected mice and in SMB-S15 cells, leading to increases of acetylating forms of SOD2 and ATP5β that subsequently induce increase of intracellular ROS and reduction of ATP [20]. Aberrant alterations of acetylation modi cations for other proteins have been also found in the brain tissues or the models in vitro of several neurodegenerative diseases, e.g., tau, microtubules, SOD1 [21][22][23].…”
Section: Introductionmentioning
confidence: 71%
“…Previously, we have described that the levels and activities of Sirt1, a class III histone deacetylase, were remarkably decreased in the brains of different scrapie infected rodent models and in a prion infected cell line SMB-S15, resulting in increases of the acetylating forms of some Sirt1 target proteins, such as P53, PGC-1, and STAT3 [19]. Recently, we have also con rmed the declined levels of Sirt3 in the brain tissues of several scrapie infected mice and in SMB-S15 cells, leading to increases of acetylating forms of SOD2 and ATP5β that subsequently induce increase of intracellular ROS and reduction of ATP [20]. Aberrant alterations of acetylation modi cations for other proteins have been also found in the brain tissues or the models in vitro of several neurodegenerative diseases, e.g., tau, microtubules, SOD1 [21][22][23].…”
Section: Introductionmentioning
confidence: 71%
“…Low levels of brain Sirt1 and Sirt3 have been addressed in various prion-infected rodent models, leading to a decrease of deacetylating activity and increases of acetylated forms of a series of target proteins. , Translocase of outer mitochondrial membrane 20 (TOMM20) is a receptor and a key subunit of the TOM complex, which is important to the importing of mitochondrial proteins . Double-staining IFAs with anti-Sirt3 and anti-Tomm20 illustrated morphological colocalization of these two signals in SMB cells, highlighting the distribution of Sirt3 in mitochondria (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has revealed aberrant alterations in the global profiles of the brain acetylated proteins by proteomics during prion infection in scrapie mouse models, showing remarkably inhibited acetylation in the early stage and relatively enhanced acetylation in the late stage . Two major components in the sirtuin family, Sirt3 and Sirt1, are markedly dysregulated in the brains of prion-infected animal and cell models. , In this report, we have identified that along with the reductions of the level and activity of Sirt3, the acetylated forms of several key enzymes in oxidative phosphorylation increase in the brains infected with scrapie agents at the terminal stage and in the prion-infected cell model. We also provide evidence that the decreased Sirt3 activity is associated with the increase of SUMOylation and decrease of SENP during prion infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations